Opportunities and challenges for anti-CD47 antibodies in hematological malignancies - Xu, Yilan; Jiang, Panruo; Xu, Zhenyan; Ye, Haige (Frontiers in Immunology, 2024)
CD47 is a cell-surface ligand that is overexpressed in various malignancies and that binds to SIRPα on macrophages to promote tumor cell evasion of phagocytosis.Blocking the CD47-SIRPα axis can increase the phagocytosis of macrophages to exert antitumor effects. CD47-based immunotherapy is a current research focus. The combination of anti-CD47 antibodies with other drugs has shown encouraging response rates in patients with hematological tumors, but side effects also occur.Bispecific antibodies and SIRPα/Fc fusion proteins appear to balance the efficacy and safety of treatment. We review the latest clinical research advances and discuss the opportunities and challenges associated with CD47-based immunotherapy for hematological malignancies.